Dielectrics, capacitors, electric circuits, circuit boards, equipment, and power storage devices
By adjusting the molar ratio of Hf, Zr and Ga, oxide materials with excellent dielectric properties were prepared, which solved the problem of residual polarization of HfO2dielectric in capacitor, and achieved the improvement of energy storage capacity and the performance of nonlinear dielectric characteristics.
Patent Information
- Application Number
- JP2024576353
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-10-18
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-23
AI Technical Summary
Existing HfO2dielectrics are prone to residual polarization problems in capacitor applications, which makes it difficult to increase the energy storage capacity.
By adjusting the molar ratio of Hf, Zr and Ga, ensuring that the molar ratio of Zr/(Hf+Zr) is between 0.2 and 1 and the molar ratio of Ga/(Hf+Zr+Ga) is between 0 and 0.14, an oxide material with excellent dielectric properties is prepared.
Reduces residual polarization of dielectric, improves energy storage capacity, and exhibits nonlinear dielectric properties in high-voltage applications.
Smart Images

Figure 0007656849000002 
Figure 0007656849000003 
Figure 0007656849000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to dielectrics, capacitors, electric circuits, circuit boards, equipment, and power storage devices. [Background technology]
[0002] It has been known that the dielectric properties of HfO2 can be changed by substituting a part of Hf with other elements. For example, Non-Patent Document 1 describes that various dopants such as Si, Zr, Al, Y, Gd, Sr, and La impart ferroelectricity and antiferroelectricity to HfO2 thin films.
[0003] Patent Document 1 describes a capacitor having a dielectric layer made of a metal oxide containing Hf, Bi, and an element having a valence of five or more. The element having a valence of five or more is selected from, for example, Nb, Ta, Mo, and W. This capacitor can exhibit antiferroelectricity. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 208340 [Non-patent literature]
[0005] [Non-Patent Document 1] Advanced Materials, (Germany), 2015, 27, 1811-1831 Summary of the Invention [Problem to be solved by the invention]
[0006] The present disclosure provides an advantageous dielectric material from the standpoint of bulk energy storage. [Means for solving the problem]
[0007] The dielectric material of the present disclosure is Hafnium, zirconium, and gallium-containing oxides, the molar ratio of the zirconium content to the sum of the hafnium content and the zirconium content is 0.2 or more and less than 1; The molar ratio of the gallium content to the sum of the hafnium content, the zirconium content, and the gallium content is greater than 0 and less than 0.14. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a dielectric material that is advantageous from the viewpoint of large-capacity energy storage. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a capacitor according to the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of a capacitor according to the present disclosure. [Figure 3A] FIG. 3A is a diagram illustrating a schematic example of an electric circuit according to the present disclosure. [Figure 3B] FIG. 3B is a diagram illustrating a schematic diagram of an example of the circuit board of the present disclosure. [Figure 3C] FIG. 3C is a schematic diagram of an example of an apparatus of the present disclosure. [Figure 3D] FIG. 3D is a diagram illustrating a schematic diagram of an example of an electricity storage device according to the present disclosure. [Figure 4] FIG. 4 is a graph showing an X-ray diffraction (XRD) pattern of the dielectric material according to Example 1. [Diagram 5] FIG. 5 is a graph showing the relationship between polarization and electric field intensity in the capacitor according to the first embodiment. [Figure 6] FIG. 6 is a graph showing the relationship between polarization and electric field intensity in the capacitor according to Example 6. [Figure 7] FIG. 7 is a graph showing the relationship between polarization and electric field intensity in the capacitor according to Comparative Example 1. In FIG. [Figure 8]FIG. 8 is a graph showing the relationship between the molar ratio Ga / (Hf+Zr+Ga) and the molar ratio Zr / (Hf+Zr) in the dielectric materials according to the examples and the comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Findings on which this disclosure is based) When a voltage is applied to an antiferroelectric, the dielectric constant of the antiferroelectric increases as the electric field strength increases, and the antiferroelectric has nonlinear dielectric properties. It is expected that antiferroelectrics will be used in high-voltage applications. Paraelectrics also have a constant dielectric constant with respect to changes in electric field strength, which is advantageous in terms of ease of device design.
[0011] HfO2 is likely to contain both antiferroelectric and ferroelectric phases. When a ferroelectric phase is present, remnant polarization is likely to occur. For this reason, when HfO2 is used for a capacitor, it is difficult to increase the energy storage capacity. For example, when HfO2 that partially contains a ferroelectric phase is used for the dielectric layer of a capacitor, remnant polarization occurs even when the external electric field is zero. This remnant polarization tends to reduce the energy output when the capacitor is discharged.
[0012] In view of these circumstances, the present inventors have conducted extensive research into whether it is possible to increase the energy storage capacity of a dielectric material containing an oxide containing hafnium. As a result of extensive trial and error, the present inventors have newly discovered that the remanent polarization of a dielectric material can be reduced relative to the maximum polarization by containing an oxide containing hafnium, zirconium, and gallium and adjusting the contents of these elements to a predetermined relationship. Based on this new knowledge, the present inventors have devised the dielectric material of the present disclosure.
[0013] (Embodiment) Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0014] The dielectric of the present disclosure includes an oxide containing hafnium, zirconium, and gallium. In the dielectric, the molar ratio Zr / (Hf+Zr) of the zirconium content to the sum of the hafnium content and the zirconium content is 0.2 or more and less than 1. In addition, the molar ratio Ga / (Hf+Zr+Ga) of the gallium content to the sum of the hafnium content, the zirconium content, and the gallium content is greater than 0 and less than 0.14. With this configuration, the remanent polarization of the dielectric is likely to be smaller than the maximum polarization, and the dielectric is likely to have advantageous characteristics in terms of increasing the energy storage capacity.
[0015] It is believed that when the contents of hafnium, zirconium, and gallium in the dielectric are adjusted to fall within the above ranges, the amount of ferroelectric phase contained in the dielectric tends to be small, and the remanent polarization of the dielectric tends to be small relative to the maximum polarization.
[0016] The relationship of the hafnium, zirconium, and gallium contents in the dielectric may be determined according to methods such as, for example, X-ray photoelectron spectroscopy (XPS) and energy dispersive X-ray spectroscopy (EDX).
[0017] In the dielectric, for example, the molar ratio Zr / (Hf+Zr) may be 0.2 or more and 0.8 or less, and the molar ratio Ga / (Hf+Zr+Ga) may be 0.06 or less. In this case, the dielectric properties of the dielectric become close to antiferroelectricity, and the relative dielectric constant of the dielectric may increase as the electric field strength increases. Therefore, the dielectric is likely to have more advantageous properties in terms of increasing the energy storage capacity. The dielectric may be promising, for example, for high voltage applications.
[0018] In a dielectric, for example, the molar ratio Zr / (Hf + Zr) may be greater than 0.8 and less than 1, and the molar ratio Ga / (Hf + Zr + Ga) may be greater than 0.06 and less than 0.14. In this case, although the dielectric properties of the dielectric are close to normal dielectricity, the residual polarization is small and the maximum polarization tends to be large. Therefore, the dielectric is likely to have advantageous properties from the viewpoint of increasing the energy storage capacity. In addition, since the amount of change in the relative permittivity of the dielectric tends to be small even when the electric field strength changes, the design of a device using the dielectric can be facilitated.
[0019] The dielectric has, for example, a composition represented by 1-x-y Zr x Ga y O 2±δ This composition satisfies the conditions of 0.2 ≦ x / (1 - y) < 1 and 0 < y < 0.14. In this case, the dielectric is more likely to have advantageous properties from the viewpoint of increasing the energy storage capacity.
[0020] In the above composition, δ is not limited to a specific value. δ is, for example, a value for maintaining the electrical neutrality of the dielectric. For example, when the dielectric is produced by a vapor phase method, anion deficiency is likely to occur and a deviation from the stoichiometric ratio is likely to occur. In the above composition, for example, the condition of 0.00 ≦ δ ≦ 0.07 is satisfied.
[0021] The above composition preferably satisfies the conditions of 0.2 ≦ x / (1 - y) ≦ 0.8 and 0 < y ≦ 0.06. In this case, the dielectric properties of the dielectric tend to be close to anti-ferroelectricity, and when the electric field strength increases, the relative permittivity of the dielectric may increase. Therefore, the dielectric is more likely to have advantageous properties from the viewpoint of increasing the energy storage capacity. The dielectric may be promising, for example, for high-voltage applications.
[0022] The above composition may satisfy the conditions of 0.8 < x / (1 - y) < 1 and 0.06 < y < 0.14. In this case, although the dielectric properties of the dielectric tend to be close to normal dielectricity, the residual polarization is small and the maximum polarization tends to be large. Therefore, the dielectric is likely to have advantageous properties from the viewpoint of increasing the energy storage capacity. In addition, since the change amount of the relative permittivity of the dielectric tends to be small even when the electric field strength changes, the design of a device using the dielectric can be facilitated.
[0023] The dielectric may be composed of a single phase or may be composed of a plurality of phases.
[0024] The crystal structure contained in the dielectric is not limited to a specific crystal structure. The dielectric includes, for example, a fluorite structure. In this case, the dielectric is more likely to have advantageous properties from the viewpoint of increasing the energy storage capacity.
[0025] The dielectric includes, for example, at least one selected from the group consisting of a tetragonal phase and an orthorhombic phase. In this case, the dielectric is more likely to have advantageous properties from the viewpoint of increasing the energy storage capacity.
[0026] The method for manufacturing the dielectric is not limited to a specific method. The dielectric can be manufactured, for example, by a vacuum process such as a high-frequency (RF) magnetron sputtering method, pulsed laser deposition (PLD), atomic layer deposition (ALD), and chemical vapor deposition (CVD). The dielectric may be manufactured by a wet process such as a chemical solution deposition method (CSD), a sol-gel method, and a hydrothermal method.
[0027] The form of the dielectric is not limited to a specific form. The dielectric forms, for example, a layer or a film.
[0028] Fig. 1 is a cross-sectional view showing an example of a capacitor of the present disclosure. As shown in Fig. 1, capacitor 1a includes first electrode 11, second electrode 12, and dielectric 20. Dielectric 20 is disposed between first electrode 11 and second electrode 12. Capacitor 1a includes dielectric 20, so that it is easy to store a large amount of energy.
[0029] In the capacitor 1a, the first electrode 11, the second electrode 12, and the dielectric 20 are not limited to a specific form. Each of the first electrode 11, the second electrode 12, and the dielectric 20 forms, for example, a layer or a film.
[0030] The thickness of the first electrode 11 is not limited to a specific value. The thickness of the first electrode 11 is, for example, 50 nm or more. This makes it easy for the internal resistance of the capacitor 1a to be small. The thickness of the first electrode 11 is, for example, 500 nm or less. This makes it easy for the overall capacitance density to be large when multiple capacitors 1a are integrated and used.
[0031] There is no particular limitation to the material of the first electrode 11. The first electrode 11 contains, for example, at least one selected from the group consisting of aluminum, titanium nitride, titanium oxide, molybdenum, tungsten, tantalum, zirconium, hafnium, niobium, titanium, silicon, zinc oxide, indium oxide, and tin oxide.
[0032] The thickness of the second electrode 12 is not limited to a specific value. The thickness of the second electrode 12 is, for example, 50 nm or more. This makes it easy for the internal resistance of the capacitor 1a to be small. The thickness of the second electrode 12 is, for example, 500 nm or less. This makes it easy for the overall capacitance density to be large when a plurality of capacitors 1a are integrated and used.
[0033] The material of the second electrode 12 is not limited to a specific material. The second electrode 12 includes, for example, at least one selected from the group consisting of a conductive polymer, manganese oxide, zinc oxide, indium oxide, tin oxide, titanium nitride, titanium oxide, an electrolyte, and polysilicon. Examples of the conductive polymer include polythiophene, polyaniline, polypyrrole, and derivatives thereof.
[0034] 1, the capacitor 1a further includes, for example, a support 30. The first electrode 11 is disposed on, for example, the support 30. This allows the laminate including the first electrode 11, the dielectric 20, and the second electrode 12 to be supported by the support 30, which tends to increase the mechanical strength of the capacitor 1a. The support 30 can be used, for example, as a base material for forming the first electrode 11. In the capacitor 1a, the support 30 may be omitted.
[0035] The support 30 is not limited to a specific support. The support 30 may be a conductor, a semiconductor, or an insulator. When the support 30 is a conductor, the support 30 and the first electrode 11 may be integrated together.
[0036] The thickness of the support 30 is not limited to a specific value and may be 50 nm or more and 500 nm or less, or may be greater than 500 nm.
[0037] An example of a method for manufacturing the capacitor 1a will be described. First, the first electrode 11 is formed on the main surface of the support 30. For example, a vacuum process, plating, or coating can be applied to form the first electrode 11. Examples of the vacuum process include DC sputtering, RF magnetron sputtering, pulsed laser deposition (PLD), atomic layer deposition (ALD), and chemical vapor deposition (CVD). The support 30 may be made of a metal foil such as an aluminum foil or a zirconium foil, and the support 30 and the first electrode 11 may be integrally formed.
[0038] Next, a film of the dielectric 20 is formed on the first electrode 11. In forming the film of the dielectric 20, a rapid thermal anneal (RTA) process may be performed on the amorphous precursor of the dielectric 20 to promote crystallization of the dielectric 20.
[0039] Next, the second electrode 12 is formed on the dielectric 20. The second electrode 12 can be formed by a vacuum process, plating, or coating, similarly to the first electrode 11. In this manner, the capacitor 1a can be manufactured.
[0040] Fig. 2 is a cross-sectional view showing another example of a capacitor according to the present disclosure. Capacitor 1b shown in Fig. 2 is configured similarly to capacitor 1a, except for parts that will be particularly described. Components of capacitor 1b that are the same as or correspond to those of capacitor 1a are given the same reference numerals, and detailed description will be omitted. The description of capacitor 1a also applies to capacitor 1b, unless technically inconsistent.
[0041] 2, in capacitor 1b, at least a part of first electrode 11 is porous. With such a configuration, the surface area of first electrode 11 tends to be large, and the capacitance of capacitor 1b tends to be high. Therefore, capacitor 1b tends to store a large amount of energy. Such a porous structure can be formed, for example, by etching metal foil and sintering powder.
[0042] 2, for example, a film of a dielectric 20 is formed on the surface of a porous portion of the first electrode 11. In this case, the method for forming the dielectric 20 can be an atomic layer deposition method (ALD method) or a chemical vapor deposition method such as a CVD method or a mist CVD method.
[0043] In the capacitor 1b, the second electrode 12 includes, for example, a conductor 12a and an electrolyte 12b. For example, the electrolyte 12b is disposed between the first electrode 11 and the conductor 12a. In the capacitor 1b, the electrolyte 12b is disposed so as to fill, for example, the voids around the porous portion of the first electrode 11. The electrolyte 12b includes, for example, at least one selected from the group consisting of manganese oxide, an electrolytic solution, and a conductive polymer. Examples of the conductive polymer include polypyrrole, polythiophene, polyaniline, and derivatives thereof. The electrolyte 12b may be a manganese compound such as manganese oxide. The electrolyte 12b may include a solid electrolyte.
[0044] As shown in FIG. 3A, for example, an electric circuit 3 including a capacitor 1a can be provided. The electric circuit 3 is not limited to a specific circuit as long as it includes the capacitor 1a. The electric circuit 3 may be an active circuit or a passive circuit. The electric circuit 3 may be a discharge circuit, a smoothing circuit, a decoupling circuit, or a coupling circuit. Since the electric circuit 3 includes the capacitor 1a, the electric circuit 3 is likely to have desired characteristics. The electric circuit 3 may include a capacitor 1b instead of the capacitor 1a.
[0045] 3B, for example, a circuit board 5 including a capacitor 1a can be provided. Since the circuit board 5 includes the capacitor 1a, the design of the circuit board 5 is easy. For example, an electric circuit 3 including the capacitor 1a is formed in the circuit board 5. The circuit board 5 may include a capacitor 1b instead of the capacitor 1a.
[0046] As shown in Fig. 3C, for example, device 7 including capacitor 1a can be provided. Since device 7 includes capacitor 1a, device 7 is likely to have desired characteristics. For example, device 7 includes circuit board 5 including capacitor 1a. Device 7 is, for example, an information terminal such as a smartphone or a tablet PC. Device 7 may include capacitor 1b instead of capacitor 1a.
[0047] As shown in FIG. 3D , for example, an electricity storage device 9 including a capacitor 1a can be provided. Since the electricity storage device 9 includes the capacitor 1a, the electricity storage device 9 is likely to have desired characteristics. For example, an electricity storage system 50 can be provided using the electricity storage device 9. The electricity storage system 50 includes the electricity storage device 9 and a power generation device 2. In the electricity storage system 50, electricity generated by the power generation device 2 is stored in the electricity storage device 9. The power generation device 2 is, for example, a device for solar power generation or wind power generation. The electricity storage device 9 is, for example, a device including a lithium ion battery or a lead acid battery. The electricity storage device 9 may include a capacitor 1b instead of the capacitor 1a.
[0048] The applications of the dielectric material are not limited to capacitors. For example, the dielectric material may be used in electro-optical devices, memory devices, transistors, ferroelectric data storage devices, piezoelectric devices, pyroelectric devices, and the like.
[0049] (Additional Note) From the above description, the following techniques are disclosed. (Technology 1) Hafnium, zirconium, and gallium-containing oxides, the molar ratio of the zirconium content to the sum of the hafnium content and the zirconium content is 0.2 or more and less than 1; The molar ratio of the gallium content to the sum of the hafnium content, the zirconium content, and the gallium content is greater than 0 and less than 0.14; Dielectric. (Technology 2) the molar ratio of the zirconium content to the sum of the hafnium content and the zirconium content is 0.2 or more and 0.8 or less; The molar ratio of the gallium content to the sum of the hafnium content, the zirconium content, and the gallium content is greater than 0 and less than or equal to 0.06; The dielectric material according to technique 1. (Technology 3) The dielectric is Hf 1-x-y Zrx Ga y O 2±δ having a composition represented by wherein the composition satisfies the conditions of 0.2 ≦ x / (1 - y) < 1 and 0 < y < 0.14, the dielectric according to Technique 1 or 2. (Technique 4) wherein the composition further satisfies the conditions of 0.2 ≦ x / (1 - y) ≦ 0.8 and 0 < y ≦ 0.06, the dielectric according to Technique 3. (Technique 5) wherein the dielectric includes a fluorite structure, the dielectric according to any one of Techniques 1 to 4. (Technique 6) wherein the dielectric includes at least one selected from the group consisting of a tetragonal phase and an orthorhombic phase, the dielectric according to any one of Techniques 1 to 5. (Technique 7) a first electrode, a second electrode, and a dielectric disposed between the first electrode and the second electrode, wherein the dielectric is the dielectric according to any one of Techniques 1 to 6, a capacitor. (Technique 8) wherein the first electrode includes at least one selected from the group consisting of aluminum, titanium nitride, titanium oxide, molybdenum, tungsten, tantalum, zirconium, hafnium, niobium, titanium, silicon, zinc oxide, indium oxide, and tin oxide, the capacitor according to Technique 7. (Technique 9) wherein the second electrode includes at least one selected from the group consisting of a conductive polymer, manganese oxide, zinc oxide, indium oxide, tin oxide, titanium nitride, titanium oxide, an electrolyte, and polysilicon, the capacitor according to Technique 7. (Technique 10) an electric circuit including the capacitor according to any one of Techniques 7 to 9. (Technique 11) A circuit board comprising the capacitor according to any one of techniques 7 to 9. (Technology 12) A device comprising the capacitor according to any one of techniques 7 to 9. (Technology 13) An electricity storage device comprising the capacitor according to any one of techniques 7 to 9. EXAMPLES
[0050] The present disclosure will be described in more detail below with reference to examples. Note that the following examples are merely illustrative and the present disclosure is not limited to the following examples.
[0051] Example 1 A polycrystalline TiN thin film was formed to a thickness of 70 nm on a single crystal substrate having a Si(100) surface by RF magnetron sputtering to obtain a first electrode layer. Next, Hf 0.474 Zr 0.474 Ga 0.051 A dielectric layer having a composition of HfO2, ZrO2, and Ga2O3 was formed with a thickness of 15 nm. At this point, the dielectric in the dielectric layer was an amorphous paraelectric. The composition of the dielectric layer was determined based on the ALD film formation conditions for forming the dielectric layer, with reference to the Growth Per Cycle (GPC) when HfO2, ZrO2, and Ga2O3 were formed in the ALD. Next, a laminate including a single crystal substrate having a Si(100) surface, a first electrode layer, and a dielectric layer was heated in a nitrogen atmosphere at 500°C for 60 seconds, and RTA was performed. It is believed that this heating process changed the structure of the dielectric layer from amorphous to a crystal structure of a tetragonal phase exhibiting antiferroelectricity or a rhombic phase exhibiting ferroelectricity. In this way, the dielectric according to Example 1 was obtained. Thereafter, a thin Au film was formed with a thickness of 150 nm on the dielectric layer by vacuum deposition to obtain a second electrode layer. In this way, the capacitor according to Example 1 was produced.
[0052] XRD measurement was performed on the sample obtained from the dielectric material according to Example 1 using an X-ray diffraction (XRD) device Aeris manufactured by Malvern Panalytical. The results are shown in FIG. 4. The vertical axis of FIG. 4 is the diffraction intensity in arbitrary units, and the horizontal axis is the diffraction angle 2θ. In FIG. 4, the notation "m" indicates the diffraction angle 2θ corresponding to the monoclinic crystal, the notation "o / t / c" indicates the diffraction angle 2θ corresponding to the orthogonal crystal, the tetragonal crystal, or the cubic crystal, and the notation "sub." indicates the diffraction angle corresponding to the substrate or the first electrode layer.
[0053] Using a ferroelectric tester Premier II manufactured by Radiant Technology, a Polarization-Electric field (PE) curve measurement was performed on the capacitor according to Example 1 to evaluate the dielectric properties of the dielectric according to Example 1. The results are shown in Fig. 5. The vertical axis of Fig. 5 indicates polarization, and the horizontal axis indicates electric field intensity. The maximum polarization P max and the remanent polarization P, which is the polarization when the electric field strength becomes 0 as the electric field strength decreases. r Identify the maximum polarization P max From the residual polarization P r The difference (P max -P r ) was obtained. A large difference is advantageous from the viewpoint of large-capacity energy storage. The results are shown in Table 1. In addition, the shape of the PE curve was used to determine whether the dielectric properties of the dielectric were closer to antiferroelectricity, paraelectricity, or ferroelectricity, and evaluated as follows. The results are shown in Table 1. A: The dielectric properties of the dielectric are close to antiferroelectric. B: The dielectric properties of the dielectric are close to paraelectric. C: The dielectric properties of the dielectric are close to ferroelectric.
[0054] As shown in FIG. 4, no monoclinic crystals were confirmed in the dielectric of Example 1, and the main phase of this dielectric was confirmed to be at least one selected from the group consisting of orthorhombic, tetragonal, and cubic crystals. This dielectric is considered to include a fluorite structure. As shown in FIG. 5, the remanent polarization P rIt is considered that the dielectric of Example 1 contains a small amount of ferroelectric phase. According to the shape of the PE curve shown in FIG. 5, the dielectric characteristic of the dielectric of Example 1 is close to antiferroelectricity. max -P r ) is large, and it is considered that the dielectric material according to Example 1 has a small amount of ferroelectric phase.
[0055] Example 2 The composition of the dielectric layer is Hf 0.488 Zr 0.488 Ga 0.024 The dielectric and capacitor of Example 2 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was O2. The dielectric and capacitor of Example 2 were evaluated in the same manner as in Example 1. The results are shown in Table 1. In the dielectric of Example 2, the remanent polarization P r is small, and the difference (P max -P r ) was large. The dielectric properties of the dielectric material according to Example 2 are close to antiferroelectric, and it is considered that the dielectric material according to Example 2 has a small amount of ferroelectric phase.
[0056] Example 3 The composition of the dielectric layer is Hf 0.237 Zr 0.711 Ga 0.051 The dielectric and capacitor of Example 3 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was O2. The dielectric and capacitor of Example 3 were evaluated in the same manner as in Example 1. The results are shown in Table 1. In the dielectric of Example 3, the remanent polarization P r is small, and the difference (P max -P r ) was large. The dielectric properties of the dielectric material according to Example 3 are close to antiferroelectricity, and it is considered that the dielectric material according to Example 3 has a small amount of ferroelectric phase.
[0057] Example 4 The composition of the dielectric layer is Hf 0.243 Zr 0.730 Ga 0.026The dielectric and capacitor of Example 4 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was O2. The dielectric and capacitor of Example 4 were evaluated in the same manner as in Example 1. The results are shown in Table 1. In the dielectric of Example 4, the remanent polarization P r is small, and the difference (P max -P r ) was large. The dielectric properties of the dielectric material according to Example 4 are close to antiferroelectric, and it is considered that the dielectric material according to Example 4 has a small amount of ferroelectric phase.
[0058] Example 5 The composition of the dielectric layer is Hf 0.659 Zr 0.293 Ga 0.048 The dielectric and capacitor of Example 5 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was O2. The dielectric and capacitor of Example 5 were evaluated in the same manner as in Example 1. The results are shown in Table 1. In the dielectric of Example 5, the remanent polarization P r is small, and the difference (P max -P r ) was large. In addition, the dielectric properties of the dielectric material according to Example 5 are close to antiferroelectricity, and it is considered that the dielectric material according to Example 5 has a small amount of ferroelectric phase.
[0059] Example 6 The composition of the dielectric layer is Hf 0.462 Zr 0.462 Ga 0.075 The dielectric and capacitor of Example 6 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was O2. The dielectric and capacitor of Example 6 were evaluated in the same manner as in Example 1. The results are shown in Table 1. FIG. 6 is a graph showing the relationship between polarization and electric field strength in the capacitor of Example 6. The vertical axis of FIG. 6 shows polarization, and the horizontal axis shows electric field strength. In the capacitor of Example 6, the remanent polarization P r It is considered that the dielectric material according to Example 6 contains a small amount of ferroelectric phase. As shown in FIG. 6, in the capacitor according to Example 6, the PE curve is linear, and the dielectric properties of the dielectric material are close to paraelectric. On the other hand, the maximum polarization P maxSince the dielectric is large, it is considered that the dielectric also contains a certain proportion of antiferroelectric phase. As mentioned above, the dielectric properties of the dielectric are close to paraelectric, but the difference (P max -P r ) is large, and it is considered that the dielectric material according to Example 6 contains a small amount of ferroelectric phase.
[0060] Example 7 The composition of the dielectric layer is Hf 0.451 Zr 0.451 Ga 0.098 The dielectric and capacitor of Example 7 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was O2. The dielectric and capacitor of Example 7 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric of Example 7 are close to paraelectric, but the difference (P max -P r ) is large, and it is considered that the dielectric material according to Example 7 contains a small amount of ferroelectric phase.
[0061] Example 8 The composition of the dielectric layer is Hf 0.231 Zr 0.694 Ga 0.075 The dielectric and capacitor of Example 8 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was O2. The dielectric and capacitor of Example 8 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric of Example 8 are close to paraelectric, but the difference (P max -P r ) is large, and it is considered that the dielectric material according to Example 8 contains a small amount of ferroelectric phase.
[0062] Example 9 The composition of the dielectric layer is Hf 0.226 Zr 0.677 Ga 0.098 The dielectric and capacitor of Example 9 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was O2. The dielectric and capacitor of Example 9 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric of Example 9 are close to paraelectric, but the difference (P max -Pr ) is large, and it is considered that the dielectric material according to Example 9 contains a small amount of ferroelectric phase.
[0063] Comparative Example 1 The composition of the dielectric layer is Hf 0.500 Zr 0.500 The dielectric and capacitor according to Comparative Example 1 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the temperature was O2. The dielectric and capacitor according to Comparative Example 1 were evaluated in the same manner as in Example 1. The results are shown in Table 1. FIG. 7 is a graph showing the relationship between polarization and electric field strength in the capacitor according to Comparative Example 1. The vertical axis of FIG. 7 represents polarization, and the horizontal axis represents electric field strength. As shown in FIG. 7, the dielectric characteristics of the dielectric according to Comparative Example 1 are close to ferroelectricity, and the remanent polarization P r Therefore, the difference (P max -P r ) is small, and it is difficult to say that this dielectric is advantageous from the viewpoint of large-capacity energy storage.
[0064] Comparative Example 2 The composition of the dielectric layer is Hf 0.250 Zr 0.750 A dielectric and a capacitor according to Comparative Example 2 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was 0.05%. The dielectric and the capacitor according to Comparative Example 2 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric according to Comparative Example 2 are close to ferroelectricity, and the remanent polarization P r Therefore, the difference (P max -P r ) was small. This dielectric was not advantageous from the viewpoint of large-capacity energy storage.
[0065] Comparative Example 3 The composition of the dielectric layer is Hf 0.690 Zr 0.310A dielectric and a capacitor according to Comparative Example 3 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was 0.05%. The dielectric and the capacitor according to Comparative Example 3 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric according to Comparative Example 3 were close to paraelectric, and the remanent polarization P r is small, but the maximum polarization P max Therefore, the difference (P max -P r ) was small. This dielectric was not advantageous from the viewpoint of large-capacity energy storage.
[0066] Comparative Example 4 The dielectric and capacitor according to Comparative Example 4 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that a HfO2 thin film containing neither Zr nor Ga was formed as the dielectric layer. The dielectric and capacitor according to Comparative Example 4 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric according to Comparative Example 4 were close to paraelectric, and the remanent polarization P r is small, but the maximum polarization P max Therefore, the difference (P max -P r ) was small. This dielectric was not advantageous from the viewpoint of large-capacity energy storage.
[0067] Comparative Example 5 A dielectric and a capacitor according to Comparative Example 5 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that a ZrO2 thin film containing neither Hf nor Ga was formed as the dielectric layer. The dielectric and the capacitor according to Comparative Example 5 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric characteristics of the dielectric according to Comparative Example 5 are close to antiferroelectricity, but the remanent polarization P r is large, and the difference (P max -P r ) was small. It is believed that the ferroelectric phase contained in this dielectric is not small.
[0068] Comparative Example 6 The composition of the dielectric layer is Zr0.949 Ga 0.051 The dielectric and capacitor according to Comparative Example 6 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was 0.05%. The dielectric and capacitor according to Comparative Example 6 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric according to Comparative Example 6 are close to paraelectric, and the remanent polarization P r is small, but the maximum polarization P max Therefore, the difference (P max -P r ) was small. This dielectric was not advantageous from the viewpoint of large-capacity energy storage.
[0069] Comparative Example 7 The composition of the dielectric layer is Zr 0.902 Ga 0.098 The dielectric and capacitor of Comparative Example 7 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was 0.05%. The dielectric and capacitor of Comparative Example 7 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric of Comparative Example 7 are close to paraelectric, and the remanent polarization P r is small, but the maximum polarization P max Therefore, the difference (P max -P r ) was small. This dielectric was not advantageous from the viewpoint of large-capacity energy storage.
[0070] Comparative Example 8 The composition of the dielectric layer is Zr 0.860 Ga 0.140 The dielectric and capacitor of Comparative Example 8 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was 0.05%. The dielectric and capacitor of Comparative Example 8 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric of Comparative Example 8 are close to paraelectric, and the remanent polarization P r is small, but the maximum polarization P max Therefore, the difference (P max -P r) was small. This dielectric was not advantageous from the viewpoint of large-capacity energy storage.
[0071] Comparative Example 9 The composition of the dielectric layer is Hf 0.430 Zr 0.430 Ga 0.140 The dielectric and capacitor of Comparative Example 9 were obtained in the same manner as in Example 1, except that the ALD film formation conditions were adjusted so that the oxygen concentration was 0.05%. The dielectric and capacitor of Comparative Example 9 were evaluated in the same manner as in Example 1. The results are shown in Table 1. The dielectric properties of the dielectric of Comparative Example 9 are close to paraelectric, and the remanent polarization P r is small, but the maximum polarization P max Therefore, the difference (P max -P r ) was small. This dielectric was not advantageous from the viewpoint of large-capacity energy storage.
[0072] As shown in Table 1, the P of the dielectrics according to Examples 1 to 9 max -P rThe value of is large, and the amount of ferroelectric phase contained in these dielectrics is small, and it is understood that they have advantageous properties from the viewpoint of large-capacity energy storage. FIG. 8 is a graph showing the relationship between the molar ratio Ga / (Hf+Zr+Ga) and the molar ratio Zr / (Hf+Zr) in the dielectrics according to the examples and comparative examples. In FIG. 8, the vertical axis shows the molar ratio Ga / (Hf+Zr+Ga), and the horizontal axis shows the molar ratio Zr / (Hf+Zr). In FIG. 8, the plots of "◯" show the examples, and the plots of "×" show the comparative examples. In Table 1, the symbols attached to each plot in FIG. 8 are listed for the examples or comparative examples corresponding to the symbols. As shown by the dashed rectangle in FIG. 8, in the dielectrics according to the examples, the molar ratio Zr / (Hf+Zr) was 0.2 or more and less than 1, and the molar ratio Ga / (Hf+Zr+Ga) was greater than 0 and less than 0.14. It was suggested that when these molar ratios are in such ranges, the dielectrics are likely to have advantageous properties from the viewpoint of large-capacity energy storage. 8, in the dielectrics according to Examples 1 to 5, the molar ratio Zr / (Hf+Zr) was 0.2 or more and 0.8 or less, and the molar ratio Ga / (Hf+Zr+Ga) was greater than 0 and less than 0.06. It was suggested that when these molar ratios are in such ranges, the dielectrics tend to have more advantageous characteristics in terms of large-capacity energy storage.
[0073] [Table 1] [Industrial Applicability]
[0074] The dielectric material of the present disclosure contains a small amount of ferroelectric phase and tends to have a low remanent polarization, which is advantageous from the viewpoint of large capacity energy storage.
Claims
1. Hafnium, zirconium, and gallium-containing oxides, the molar ratio of the zirconium content to the sum of the hafnium content and the zirconium content is 0.2 or more and less than 1; The molar ratio of the gallium content to the sum of the hafnium content, the zirconium content, and the gallium content is greater than 0 and less than 0.14; Dielectric.
2. a molar ratio of the zirconium content to the sum of the hafnium content and the zirconium content is 0.2 or more and 0.8 or less; The molar ratio of the gallium content to the sum of the hafnium content, the zirconium content, and the gallium content is greater than 0 and less than or equal to 0.06; The dielectric material according to claim 1 .
3. The dielectric is Hf 1-x-y Zr x G y O 2±δ The composition is represented by The composition satisfies the conditions of 0.2≦x / (1−y)<1 and 0<y<0.
14. The dielectric material according to claim 1 .
4. The composition further satisfies the conditions: 0.2≦x / (1−y)≦0.8 and 0<y≦0.06; The dielectric material according to claim 3 .
5. The dielectric material comprises a fluorite structure. The dielectric material according to claim 1 .
6. The dielectric material includes at least one selected from the group consisting of a tetragonal phase and an orthorhombic phase. The dielectric material according to claim 1 .
7. A first electrode; A second electrode; a dielectric disposed between the first electrode and the second electrode; The dielectric is the dielectric according to claim 1. Capacitor.
8. The first electrode contains at least one selected from the group consisting of aluminum, titanium nitride, titanium oxide, molybdenum, tungsten, tantalum, zirconium, hafnium, niobium, titanium, silicon, zinc oxide, indium oxide, and tin oxide; The capacitor of claim 7.
9. the second electrode includes at least one selected from the group consisting of a conductive polymer, manganese oxide, zinc oxide, indium oxide, tin oxide, titanium nitride, titanium oxide, an electrolyte, and polysilicon; The capacitor of claim 7.
10. An electric circuit comprising a capacitor according to any one of claims 7 to 9.
11. A circuit board comprising the capacitor according to claim 7 .
12. An apparatus comprising a capacitor according to any one of claims 7 to 9.
13. An electricity storage device comprising the capacitor according to any one of claims 7 to 9.
Citation Information
Patent Citations
Information recording medium, method for producing same, and apparatus for producing same
WO2007088682A1
Optical information recording medium, method for manufacturing the same, and target thereof
WO2009096165A1
Capacitor, method for manufacturing same, and wireless communication device using same
WO2017069059A1
CAPACITOR AND METHOD FOR MANUFACTURING HfO 2 FILM
WO2019208340A1